2021
DOI: 10.3390/plants10030468
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Legumes as a Pre-Crop on Nitrogen Nutrition and Yield in Organic Greenhouse Tomato

Abstract: An organic greenhouse crop of tomato was established in February following cultivation of cowpea (CP) or common bean (CB) for green pod production, or faba bean (FB) for green manuring. The vegetative residues of CP and CB were incorporated to the soil together with farmyard manure (FYM), prior to establishing the tomato crop. The FB plants were incorporated to the soil at anthesis together with either FYM or composted olive-mill waste (CO). Green manuring with FB resulted in higher soil mineral N levels durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 53 publications
1
3
0
Order By: Relevance
“…Similar yield responses of common beans to sub-optimal soil N availability have also been reported by Chekanai et al [ 35 ], Elkhabit [ 36 ], Karasu et al [ 37 ], and Silva et al [ 38 ], who cultivated crops for either green pods, or dry seeds. The beneficial effect of GM application for organically grown common yield seen here, is in accordance with the study of Gatsios et al [ 12 ], who also found that the incorporation of animal manure and GM, including faba beans, enhanced the yield of a subsequent tomato crop. Contrary to the above findings, in the study of Kontopoulou et al [ 3 ] GM application did not mitigate the fresh pod yield gap between organic and conventional common beans.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Similar yield responses of common beans to sub-optimal soil N availability have also been reported by Chekanai et al [ 35 ], Elkhabit [ 36 ], Karasu et al [ 37 ], and Silva et al [ 38 ], who cultivated crops for either green pods, or dry seeds. The beneficial effect of GM application for organically grown common yield seen here, is in accordance with the study of Gatsios et al [ 12 ], who also found that the incorporation of animal manure and GM, including faba beans, enhanced the yield of a subsequent tomato crop. Contrary to the above findings, in the study of Kontopoulou et al [ 3 ] GM application did not mitigate the fresh pod yield gap between organic and conventional common beans.…”
Section: Discussionsupporting
confidence: 93%
“…Seeking solutions with the aim to achieve healthier products through eco-friendly production systems, organic cultivation practices can be considered as a solution since inorganic N and synthetic agrochemicals are avoided. According to Gatsios et al [ 10 , 11 , 12 , 13 ], N supply in organic agriculture mainly relies on green and animal manures, composts, crop rotation with legumes, and utilisation of intercropping approaches. The introduction of the above-mentioned renewable N sources into agricultural production systems can also reduce contamination of water resources with nitrates [ 14 ] and increase the diversity of soil microbiota [ 15 ], thereby fostering soil nutrient availability, productivity, and health [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Here, the authors emphasized the benefits of combining superior genetic material with strong agronomic practices to increase crop yield and quality while also contributing to the improvement of soil and environmental health. In the spirit of this concept, Gatsios et al (2021) observed tomato (Solanum lycopersicum) yields after cultivation of cowpea, cultivation of common bean (Phaseolus vulgaris), and green manuring of faba bean. The authors found that the highest tomato yields (largely driven by the number of fruit per plant) were achieved when following green manure faba bean (15.8 kg•m À2 ) then by harvested cowpea (14.5 kg•m À2 ) and harvested common bean (11.4 kg•m À2 ).…”
Section: Discussionmentioning
confidence: 99%
“…The contribution of legume green manure to N fertilization in organic farming through the biological N fixation (BNF) process has been well documented [10][11][12]. Specialized experiments that were carried out in both open fields [13][14][15] and greenhouses [16][17][18] have demonstrated that the incorporation of legume biomass into the soil can provide substantial amounts of plant available N for the following organic tomato crop. However, the cultivation and incorporation of green manure into organic greenhouses considerably reduces the available time for fruit production in the yearly cycle.…”
Section: Introductionmentioning
confidence: 99%